Fuzzy-based estimation of mixed convection heat transfer in a square cavity in the presence of an adiabatic inclined fin - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2012)
In this study, heat transfer from a square cavity in the presence of a thin inclined adiabatic fin is estimated using inputs-outputs generated from a CFD code with a fuzzy based identification procedure. The Reynolds number based on cavity length is 300 and the Richardson number is varied between 1 and 30. The top and bottom walls of the cavity are kept at constant temperature while the vertical walls are assumed to be adiabatic. The fin height, fin inclination angle, and Richardson number are considered as the input and the spatial averaged Nusselt number is taken as the output for the fuzzy model. Two data sets are used. One data set which contains 45 cases is used for estimation and another data set which contains 10 cases (not used in estimation) is used for validation purposes. The predictions using fuzzy model compare well with the CFD computations. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Mixed convection; Adiabatic fin; Fuzzy model